1975
DOI: 10.1037/h0076539
|View full text |Cite
|
Sign up to set email alerts
|

Attribution versus persuasion as a means for modifying behavior.

Abstract: The present research compared the relative effectiveness of an attribution strategy with a persuasion strategy in changing behavior. Study 1 attempted to teach fifth graders not to litter and to clean up after others. An attribution group was repeatedly told that they were neat and tidy people, a persuasion group was repeatedly told that they should be neat and tidy, and a control group received no treatment. Attribution proved considerably more effective in modifying behavior. Study 2 tried to discover whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
145
1
1

Year Published

1979
1979
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 311 publications
(152 citation statements)
references
References 26 publications
3
145
1
1
Order By: Relevance
“…A person who has been labeled (credentialled) as a nonsexist may feel Liberated from antiprejudice norms to an extent not experienced by someone not so labeled. Demonstrating such an effect would be especially interesting because previous research (e.g., Kraut, 1973;R. L. Miller, Brickman, & Bolen, 1975) has demonstrated that labels can constrain people.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A person who has been labeled (credentialled) as a nonsexist may feel Liberated from antiprejudice norms to an extent not experienced by someone not so labeled. Demonstrating such an effect would be especially interesting because previous research (e.g., Kraut, 1973;R. L. Miller, Brickman, & Bolen, 1975) has demonstrated that labels can constrain people.…”
Section: Future Directionsmentioning
confidence: 99%
“…L. Miller, Brickman, & Bolen, 1975) has demonstrated that labels can constrain people. For example, labeling someone as a helpful person has been found to lead that person to be more helpful in the future (Miller et al, 1975). Resolving the question of when labeling is constraining and when it is liberating, like that of when prior behavior is constraining and when it is liberating, could provide valuable social psychological insights.…”
Section: Future Directionsmentioning
confidence: 99%
“…A third slightly later study (Miller, Brickman, & Bolen, 1975), which remains less well known than it should be given the clarity of its applied implications, involved the direct effects of labeling on youngsters who were labeled. This study showed that whereas exhorting primary school students to refrain from a particular practice (e.g., classroom littering) had only a modest and temporary effect on behavior (objectively undeserved), communications from their teacher, the principal, and the school custodian that students deserved recognition for already showing such behavior had a larger effect, and one that continued to be apparent in the period after the "nagging versus labeling" manipulation had ended.…”
Section: Confirmation Biases: Impact Of Expectations Beliefs and Somentioning
confidence: 99%
“…Other researchers have investigated the relative effectiveness of various reinforcement programs compared with attribution retraining (Chapin & Dyck, 1976;Miller et al, 1975). The Chapin and Dyck (1976) Subsequent research has focused on the joint application of attribution and reinforcement techniques (Andrews and Debus, 1978;Blaess, 1977;Ostrove, 1977).…”
Section: Interventionmentioning
confidence: 99%
“…The basis for this approach derives from such existing clinical techniques as cognitive behavior modification (Meichenbaum, 1977), cognitive restructuring (Davidson, 1966), and rationalemotive therapy (Ellis, 1962). Studies that have induced appropriate, achievement-enhancing attribution in helpless children are growing (Andrews & Debus, 1978;Blaess, 1977;Chapin & Dyck, 1976;Dweck, 1975;Miller, Brickman, & Bolen, 1975;Ostrove, 1977;Rhodes, 1977). Dweck (1975) was the first to apply attribution retraining to remediate the performance deficits of helpless elementary school children (male and female).…”
Section: Interventionmentioning
confidence: 99%